A key role for Rac and Pak signaling in neutrophil extracellular traps (NETs) formation defines a new potential therapeutic target. Issue 2 (6th December 2017) - Gavillet, Mathilde; Martinod, Kimberly; Renella, Raffaele; Wagner, Denisa D.; Williams, David A.
Abstract: NET formation in mice (NETosis) is supported by reactive oxygen species (ROS) production by NADPH oxidase and histone hypercitrullination by peptidylarginine deiminase 4 (PAD4). Rac1 and Rac2, expressed in polymorphonuclear neutrophils (PMNs), regulate the cytoskeleton, cell shape, adhesion, and migration and are also essential components of the NADPH oxidase complex. We aimed to explore the role of the Rac signaling pathway including the upstream guanosine exchange factor (GEF) activator, Vav, and a downstream effector, the p21‐activated kinase, Pak, on NETosis in PMNs using a previously described flow‐cytometry‐based assay. Rac2 ‐/‐ PMNs showed reduced levels of citrullinated histone H3 (H3Cit)‐positive cells and defective NETosis. Rac1 Δ/Δ ; Rac2 ‐/‐ PMNs demonstrated a further reduction in PMA‐induced H3Cit levels and a more profound impairment of NETosis than deletion of Rac2 alone, suggesting an overlapping role of these two highly related proteins. Genetic knockouts of Vav1, or Vav2, did not impair H3Cit response to phorbol myristate ester (PMA) or NETosis. Combined, Vav1 and Vav3 deletions decreased H3Cit response and caused a modest but significant impairment of NETosis. Pharmacologic inhibition of Pak by two inhibitors with distinct mechanisms of action, led to reduced H3Cit levels after PMA stimulation, as well as significant inhibition of NETosis. We validated the importance of Pak using Pak2 Δ/Δ PMNs, which demonstrated significantly impaired histone H3 citrullination and NETosis. These data confirm and more comprehensively define the key role of the Rac signaling pathway in PMN NETosis. The Rac signaling cascade may represent a valuable target for inhibition of NETosis and related pathological processes.